The Contribution of Cereal Grains to Food Security and Sustainability in Africa: Potential Application of UAV in Ghana, Nigeria, Uganda, and Namibia - Raheem Dele; Dayoub Moammar; Birech Rhoda; Nakiyemba Alice (MDPI, 2022)
Africa is a net importer of food, especially cereal grains, despite the importance of agriculture in the continent. The agricultural growth in Africa has been undermined by low investment in agriculture, poor infrastructure, high population growth rate, and low adoption of technologies. The agri-food value chain in many African countries will benefit from the adoption of appropriate technologies that are available in the digital landscape to leverage the agricultural sector, make it more attractive to the teeming youth population, and to reverse rural-urban migration. Attention to indigenous cereal grains and other crops that are grown locally and processed into different local foods would ensure food security. However, the availability of these crops in the market is often reduced due to damage before harvest by pests and predators leading to economic losses for farmers. In this article, we review the literature from a multidisciplinary perspective on the relevance of African indigenous food grains to food security in general and we highlight the potential application of drones to increase the yield of cereal grains in three regions of the continent—eastern, western, and southern Africa